2017
DOI: 10.1007/s00192-017-3508-z
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical hyaluronic acid and chondroitin sulfate for recurrent urinary tract infections: systematic review and meta-analysis

Abstract: Introduction and hypothesisThe objective was to assess the efficacy of intravesical hyaluronic acid (HA) and chondroitin sulfate (CS), alone or in combination, for recurrent urinary tract infections (RUTIs) in adult female patients using a systematic review and meta-analysis.MethodsEnglish-language articles were obtained from the MEDLINE, Embase, and Cochrane databases through November 2016, by manual searching and cross-referencing. Randomized and nonrandomized trials of adult female patients with a documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…• Conflicting results Hyaluronic acid (Constantinides et al, 2004;Birder and de Groat, 2007;Cicione et al, 2014;Ciani et al, 2016;Torella et al, 2016;Goddard and Janssen, 2018)(Hills et al, 2001;Klein et al, 2010;Cusumano et al, 2011;Kranjčec et al, 2014;Domenici et al, 2016) • Reduction of adhesion • Fast effect after oral administration…”
Section: Nutraceuticalmentioning
confidence: 99%
See 1 more Smart Citation
“…• Conflicting results Hyaluronic acid (Constantinides et al, 2004;Birder and de Groat, 2007;Cicione et al, 2014;Ciani et al, 2016;Torella et al, 2016;Goddard and Janssen, 2018)(Hills et al, 2001;Klein et al, 2010;Cusumano et al, 2011;Kranjčec et al, 2014;Domenici et al, 2016) • Reduction of adhesion • Fast effect after oral administration…”
Section: Nutraceuticalmentioning
confidence: 99%
“…Recently a meta-analysis suggested that HA ± CS decreased the rate of UTI recurrence and increased the time to recurrence (Goddard and Janssen, 2018). Moreover the authors noted the safety of HA therapy even if the intravesical instillation is more invasive than other administrations (usually per os).…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…SH instillations are costly and labour intensive [23,24]. However, these costs need to be weighed against the costs of antimicrobial resistance and the costs of treatment of adverse side effects of antimicrobials in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative strategies to manage UTI s both in males and females. Data to reconstruct the figure were adopted and modified from different sources…”
Section: Management Of Utimentioning
confidence: 99%